ลักษณะบุคลิกภาพและการปฏิบัติตามบทบาทในงานของพยาบาลในโรงพยาบาลศูนย์ - อดิเรก ช่างเพียร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Personality traits are important to the work role performance of nurses. The objectives of this correlational descriptive research were to determine personality traits, work role performance, and the relationship between personality traits and work role performance among nurses in regional hospitals. The sample included 413 registered nurses who were selected using the multistage sampling method. The instruments were the Big Five Inventory Questionnaire (John & Srivastava, 1999), translated into Thai by Nuchpong (2562) and the Work Role Performance Questionnaire (Griffin, Neal, & Parker, 2007), translated into Thai by the researcher. The Cronbach’s alpha coefficients of the Big Five Inventory Questionnaire regarding openness to experience, agreeableness, openness to experience, neuroticism, and conscientiousness were 0.76, 0.76, 0.75, 0.73, and 0.70, respectively; and of the Work Role Performance Questionnaire regarding individual task proficiency, team member proficiency, organization member proficiency, individual task adaptivity, team member adaptivity, organization member adaptivity, individual task proactivity, team member proactivity, and organization member proactivity were 0.91, 0.88, 0.85, 0.86, 0.89, 0.80, 0.87, 0.72, and 0.90, respectively. Data were analyzed by using descriptive statistics and Spearman’s Rank Order Correlation coefficient.The results revealed that: 1. Nurses in regional hospital possessed the personality trait of agreeableness for 75.30 %, of conscientiousness for 13.32%, of extraversion for 5.57%, of openness to experience for 4.36% and of neuroticism for 1.45%. 2. Nurses in regional hospitals possessed individual task proficiency, team member proficiency, and organization member proficiency at high levels (x̅ = 4.18, SD = .49; x̅ = 4.24, SD = .50; x̅ = 4.04, SD = .59, respectively), and possessed high levels of individual task adaptivity and team member adaptivity (x̅ = 4.11, SD = .50; x̅ = 4.15, SD = .51, respectively), whereas they possessed organization member adaptivity at a somewhat high level (x̅ = 4.00, SD = .52). In addition, nurses possessed individual task proactivity, team member proactivity, and organization member proactivity at somewhat high levels (x̅ = 3.86, SD = .60; x̅ = 3.80, SD = .60; x̅ = 3.76, SD = .69, respectively). 3. The personality traits of openness to experience, conscientiousness, agreeableness, and extraversion had significantly positive relationships with proficiency, adaptivity, and proactivity of work role performance at low to moderate levels (rS = .12-.44, p<.01). On the other hand, the personality trait of neuroticism had significantly negative relationships with proficiency, adaptivity, and proactivity of work role performance at low to moderate levels (rS =. (-.15) - (-.31), p<.01). The results of this study can be used by nurse managers in regional hospitals to develop staff’s personality traits to promote work role performance among nurses in order to contribute to increased quality and efficiency of services.